2009
DOI: 10.1063/1.3013804
|View full text |Cite
|
Sign up to set email alerts
|

Superintegrability with third order integrals of motion, cubic algebras, and supersymmetric quantum mechanics. I. Rational function potentials

Abstract: Articles you may be interested inDeformed oscillator algebra approach of some quantum superintegrable Lissajous systems on the sphere and of their rational extensions J. Math. Phys. 56, 062102 (2015) We consider a superintegrable Hamiltonian system in a two-dimensional space with a scalar potential that allows one quadratic and one cubic integrals of motion. We construct the most general cubic algebra and we present specific realizations. We use them to calculate the energy spectrum. All classical and quantum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
127
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(132 citation statements)
references
References 44 publications
5
127
0
Order By: Relevance
“…Among these potentials cases with fourth Painlevé transcendents as revealed to lead to interesting algebraic structure formed by the integrals of motion. For more detail in the case N=3 we refer the reader to [72,73]. The explicit form of the integrals have been obtained and involving calculation lead to cubic algebra.…”
Section: Cartesian and N=4mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these potentials cases with fourth Painlevé transcendents as revealed to lead to interesting algebraic structure formed by the integrals of motion. For more detail in the case N=3 we refer the reader to [72,73]. The explicit form of the integrals have been obtained and involving calculation lead to cubic algebra.…”
Section: Cartesian and N=4mentioning
confidence: 99%
“…It has been observed that higher rank quadratic algebra can be exploited [55,27,63,93] as well. Example of polynomial algebras find applications [9,60,71,58] and in particular the cubic algebras [72,73] in regard of fourth Painlevé transcendent models. A puzzling phenomena has been noticed [73] consisting in incomplete algebraic description of the spectrum and the degeneracies for certain values of the parameters of the fourth Painlevé transcendent.The story of that problem took an interesting turn as it has been shown that it was connected [78,79,80,81] with exceptional orthogonal polynomials [90,41,42,43,85,86,44,45].…”
mentioning
confidence: 99%
“…In other words, for a two-dimensional superintegrable system, there are two integrals of the motion (A 1 , A 2 ) in addition to the Hamiltonian. The superintegrability with the second and third order integrals was the object of a series of articles [11][12][13][14][15][16][17]. The systems studied have second and third order integrals.…”
Section: Introductionmentioning
confidence: 99%
“…Up to our knowledge, the first works in which it was realized the connection between PHA (called commutator representation in these papers) and Painlevé equations were [32] and [33]. Initially, both subjects were linked with first-order SUSY QM [5,6,27]; later on, this relation was further explored for the higher-order case [8,9,[28][29][30][31][34][35][36][37].Let us remark that the need to avoid singularities in the new potential V k (x) and the requirement for the Hamiltonian H k to be Hermitian lead to some restrictions [8]: (i) first of all, the relevant transformation function has to be real, which implies that the associated factorization energy is also real; (ii) as a consequence, the spectrum of H k consists of two independent physical ladders, an infinite one departing from the ground state energy E 0 of H 0 , plus a finite one with k equidistant levels, all of which have to be placed below E 0 . Regarding PV equation, these two restrictions imply that non-singular real solutions w(z; a, b, c, d) can be obtained just for certain real parameters a, b, c, d.From the spectral design point of view, however, it would be important to overcome restriction (ii) so that some (or all) steps of the finite ladder could be placed above E 0 .…”
mentioning
confidence: 99%